Pengaruh Digitalisasi dan Teknologi terhadap Profitabilitas pada Perusahaan Multifinance di Bursa Efek Indonesia - Amilia Paramita Sari (Haka Vyza Media, 2026)
This study aims to examine the effect of digitalization and technology on the profitability of multifinance companies listed on the Indonesia Stock Exchange during the period 2021–2025. A quantitative approach using linear regression analysis is employed on four multifinance companies selected through purposive sampling, resulting in 20 observations. Digitalization and technology are proxied by technology-related investment and expense ratios, while profitability is measured using Return on Assets (ROA). The results indicate that digitalization and technology have a positive and significant effect on profitability, with a regression coefficient of 0.731 and a significance level of 0.001. The Adjusted R² value of 0.589 suggests that 58.9% of the variation in profitability can be explained by digitalization and technology. These findings imply that effective digital transformation plays a strategic role in improving financial performance and sustaining competitiveness in multifinance companies.